A Feasibility Test of a Brief Mobile Virtual Reality Meditation for Frontline Healthcare Workers in a Hospital Setting - Tarrant, Jeff; Jackson, Ray; Viczko, Jeremy (Frontiers in Virtual Reality, 2022)
The purpose of this study was to examine whether a virtual reality plus neurofeedback (VR+NF) meditation) meditation experience (experimental condition) was more effective than a standard guided audio-only meditation (control condition) in improving mood in one hundred healthcare workers. One hundred healthcare workersData collection occurred in a hospital setting participated between October, 2020 and March, 2021 at the height of the COVID-19 pandemic. Participants were alternately assigned to one of the two conditions. Before and after the meditation experience, participants completed the Brunel Mood Scale. Results indicated that both groups showed a similar and significant decrease in Anger, Tension, and Depression. On scales measuring Vigor, Fatigue, and Confusion, the VR+NF group showed decreases, while the audio-only group showed no significant change. The VR+NF group showed significant increases on the Calmness and Happiness scales, which did not change significantly in the audio-only group. These results suggest that the addition of VR and neurofeedback may increase the positive outcomes associated with standard audio-guided meditation. These increased benefits may be due to the sense of presence intrinsic to VR, the inclusion of nature based scenes in the VR experience, as well as the increased self-awareness created by the addition of neurofeedback. As the pre and post measures take place within one 50 minute session, further studies assessing the longer term changes to stress or function are needed.